On the Metabolism of Exogenous Ketones in Humans - Stubbs, Brianna J.; Cox, Pete J.; Evans, Rhys D.; Santer, Peter; Miller, Jack J.; Faull, Olivia K.; Magor-Elliott, Snapper; Hiyama, Satoshi; Stirling, Matthew; Clarke, Kieran (Frontiers in Physiology, 2017)
Background and aims: Currently there is considerable interest in ketone metabolism owing to recently reported benefits of ketosis for human health. Traditionally, ketosis has been achieved by following a high-fat, low-carbohydrate ‘ketogenic’ diet, but adherence to such diets can be difficult. An alternative way to increase blood D-β-hydroxybutyrate (D-βHB) concentrations is ketone drinks, but the metabolic effects of exogenous ketones are relatively unknown. Here, healthy human volunteers took part in three randomized metabolic studies of drinks containing a ketone ester (KE); (R)-3-hydroxybutyl-(R)-1,3-hydroxybutyrate, or ketone salts (KS); sodium plus potassium βHB. Methods and Results: In the first study, 15 participants consumed KE or KS drinks that delivered ~12 g or ~24 g of βHB. Both drinks elevated blood D-βHB concentrations (D-βHB Cmax: KE 2.8 mM, KS 1.0 mM, P < 0.001), which returned to baseline within 3-4 h. KS drinks were found to contain 50% of the L-βHB isoform, which remained elevated in blood for over 8 h, but was not detectable after 24 h. Urinary excretion of both D-βHB and L-βHB was < 1.5 % of the total βHB ingested and was in proportion to the blood AUC. D-βHB, but not L-βHB, was slowly converted to breath acetone. The KE drink decreased blood pH by 0.10 and the KS drink increased urinary pH from 5.7 to 8.5. In the second study, the effect of a meal before a KE drink on blood D-βHB concentrations was determined in 16 participants. Food lowered blood D-βHB Cmax by 33% (Fed 2.2 mM, Fasted 3.3 mM, P < 0.001), but did not alter acetoacetate or breath acetone concentrations. All ketone drinks lowered blood glucose, free fatty acid and triglyceride concentrations, and had similar effects on blood electrolytes, which remained normal. In the final study, participants were given KE over 9 h as three drinks (n = 12) or a continuous nasogastric infusion (n = 4) to maintain blood D-βHB concentrations greater than 1 mM. Both drinks and infusions gave identical D-βHB AUC of 1.3-1.4 moles.min. Conclusion: We conclude that exogenous ketone drinks are a practical, efficacious way to achieve ketosis.